2021
DOI: 10.3389/fpubh.2021.739828
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Infectious Diseases Among Travelers Between China and Foreign Countries Before and During the Early Stage of the COVID-19 Pandemic

Abstract: Background: International travel during the Coronavirus disease 2019 (COVID-19) pandemic carries a certain magnitude of infection risk both to travelers and their destination, which may be difficult to assess in the early stage. The characteristics of common infectious diseases of tourists may provide some clues to identify the high-risk travelers and protect susceptible population.Methods: From among 48,444 travelers screened at Shanghai Port, we analyzed 577 travelers with 590 infectious diseases for age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…It is hoped that various research institutions and scholars will strengthen cooperation. Based on the epidemiological investigation and medical investigation conducted at the port site, risk warning and passenger health declaration can be strengthened (China 2022 ) to screen high-risk passengers in advance (Luo et al 2021 ), so as to provide a powerful reference for on-site customs officers to carry out accurate quarantine, and provide scientific guidance and technical support for winning the “foreign defense import” port epidemic prevention and control resistance war.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that various research institutions and scholars will strengthen cooperation. Based on the epidemiological investigation and medical investigation conducted at the port site, risk warning and passenger health declaration can be strengthened (China 2022 ) to screen high-risk passengers in advance (Luo et al 2021 ), so as to provide a powerful reference for on-site customs officers to carry out accurate quarantine, and provide scientific guidance and technical support for winning the “foreign defense import” port epidemic prevention and control resistance war.…”
Section: Discussionmentioning
confidence: 99%
“…Novel respiratory pathogens such as SARS-CoV-2 have an established precedent of elevated transmissibility via high-traffic hubs of national or international travel such as airports, train stations, and cruise terminals ( Pavia 2007 ) ( Luo et al, 2021 ). Fueled by its high reproduction number, asymptomatic carriers, superspreading events, increasing socio economic globalization, and an immunologically naive population, COVID-19 has wreaked havoc across the world ( Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the virus has spread through all continents, and the World Health Organization (WHO) declared a pandemic. While the first SARS-CoV-2 outbreaks occurred in most countries in major cities including Milan [2] , Manchester [3] or Chicago [4] or high-density traffic hubs [5] , [6] , [7] , the first outbreak in Germany happened in Heinsberg , a small relatively unknown town with little to no tourism [8] . After a carnival session where a super-spread occurred, it was reported that about 3.1% of the local population was PCR positive [8] .…”
Section: Introductionmentioning
confidence: 99%